Paper 73: Patient Factors Associated with Humeral Avulsion of Glenohumeral Ligament (HAGL) Lesions: An Analysis of the MOON Shoulder Instability Cohort. Issue 7 (30th July 2022) - Zhang, Alan; Ma, C. Benjamin; Feeley, Brian; Ortiz, Shannon; Hettrich, Carolyn; Wolf, Brian; Patel, Jhillika; ,; Lansdown, Drew; Freshman, Ryan
Objectives: We sought to identify pre-operative physical exam findings, imaging findings, and surgical management trends associated with humeral avulsion of the glenohumeral ligament (HAGL) lesions by utilizing a large, multicenter orthopedic outcomes database. Methods: Patients with anterior shoulder instability who underwent surgical management from 2012 to 2020 at 11 orthopedic centers were prospectively enrolled. Patients with a HAGL lesion identified intra-operatively were compared to patients without a HAGL lesion; patients with isolated posterior HAGL lesions were excluded from data analysis. Pre-operative patient demographics, physical examination, and imaging findings were collected; intra-operative findings and surgical procedures performed were also recorded. Student's T-test, Fisher Exact test and Chi Square test were used to compare groups and determine risk factors. Logistic regression analysis was performed to determine independent risk factors associated with need for an open stabilization procedure, and odds ratio (OR) and 95% confidence interval (95% CI) were calculated. Significance was set at p<0.05. Results: From 2012 to 2020, 22 HAGL lesions were identified in 1002 patients (2.2%). Baseline demographics, including age, gender, BMI, and number of lifetime shoulder dislocations, were similar between the HAGL and non-HAGL groups. As compared to non-HAGL patients, HAGL patients were less likely to have a Hill Sachs lesion (51.8% vs. 27.3%, p=0.02) or an anterior labral tear (81.7% vs. 63.6%, p=0.03) on pre-operative MRI. On pre-operative physical examination, HAGL patients demonstrated increased external rotation when their affected arm was positioned in 90° of abduction as compared to non-HAGL patients (90° vs. 85°, p=0.01). The most common procedure performed amongst all patients was an arthroscopic Bankart repair (45.5% of the HAGL patients and 78.9% of the non-HAGL group); however, HAGL patients were more likely than non-HAGL patients to undergo an open stabilization procedure (68.2% vs. 10.7%, p<0.001) and less likely to undergo an arthroscopic stabilization procedure (72.7% vs. 94.7%, p<0.001). Additionally, HAGL lesions were independently associated with an increased risk of undergoing an open stabilization procedure (OR 31.3, 95% CI 11.0 – 88.9, p<0.001). Conclusions: Patients with anterior shoulder instability and a HAGL lesion are less likely to exhibit classic pre-operative imaging findings associated with anterior shoulder instability, such as Hill Sachs lesions or anterior labral pathology. Increased external rotation at 90° of shoulder abduction on pre-operative physical exam may suggest presence of a HAGL lesion. Other demographic factors, including age, gender, BMI, and number of lifetime shoulder dislocations, do not differ significantly between patients with and without HAGL lesions. Patients with HAGL lesions undergo open stabilization procedures more frequently than patients without HAGL lesions.